Application of Mahgoub Integral Transform to Bessel’s Differential Equations - Sabarinathan, S.; Muralidharan, D.; Selvan, A. Ponmana (Communications in Mathematics and Applications, 2021)
In this paper, we apply Mahgoub integral transform method to solve various types Bessel’s differential equations with initial conditions. Also, we provide some numerical examples to illustrate the Application of Mahgoub transform for some particular Bessel’s differential equations.
Keywords: Mahgoub transform; Bessel’s differential equations